Menangkap Imaji Perdamaian dalam Lirik-Lirik Lagu Pop - Leonardo Kiloiz Efraim Petto (FOCUS, 2020)
Grasping an image of peace by way of pop songs is certainly a challenging alter- native for anyone. Nonetheless these unassuming lyrics contain both dreams and inspi- rations to strive better for a lasting peace to be realized. The image of peace is revealed metaphorically within the lyrics and rhythm of pop songs, ergo one must first require the ability to fully comprehend said metaphors. Such Images of peace provide powerful catalysts of inspiration for listeners, which they in turn are animated to create the same images of peace. Songwriters in this regard are no less heralds envisioning and of more import contributing to the cause through their chosen media of lyrical.